The use of plasma-based deposition with ion implantation technology to produce superhard molybdenum-based coatings in a mixed (C₂H₂+N₂) atmosphere - Sobol’, O.V.; Andreev, A.A.; Mygushchenko, R.P.; Beresnev, V.M.; Meylekhov, A.A.; Postelnyk, A.A.; Kravchenko, S.A.; Tabaza, Taha A.; Safwan M. Al-Qawabah; Ubeidulla F. Al-Qawabeha; Stolbovoy, V.A.; Serdyuk, I.V.; et al. (Вопросы атомной науки и техники, 2018)
The influence of the pressure of a mixed gaseous atmosphere (80%C₂H₂+20%N₂) and the supply of a high-voltage negative potential in a pulsed form on the elemental and phase composition, structure and physico-mechanical characteristics of the vacuum-arc molybdenum-based coatings. It is shown that in the temperature deposition range 400…550 °С as a result of plasma-chemical reactions, the maximum nitrogen atoms content in the coating does not exceed 1.5 at.%. It is found, that at the maximum pressure of Р(C₂H₂+N₂)= 2.3∙10⁻¹ Pа when the γ-MoC phase is formed, an superhard state of 50.5 GPa (at a constant potential -200 V, without additional high-voltage pulse action) and 51.1 GPa (at a constant potential -200 V, with additional high-voltage pulse action) is reached. Для вакуумно-дугових покриттів на основі молібдену досліджено вплив тиску змішаної газової атмосфери (80%C₂H₂+20%N₂) і високовольтного негативного потенціалу (подається на підкладку в імпульсної формі) на елементний і фазовий склад, структуру і фізико-механічні характеристики формованого матеріалу. Показано, що в температурному інтервалі підкладки при осадженні 400…550 °С в результаті плазмохімічних реакцій максимальний вміст атомів азоту в покритті не перевищує 1,5 ат.%. Виявлено, що при найбільшому тиску Р(C₂H₂+N₂)= 2.3∙10⁻¹ Па, коли формується фаза γ-MoC, досягається надтверде стан 50,5 ГПа (при постійному потенціалі -200 В, без додаткового високовольтного імпульсного потенціалу) і 51,1 ГПа (при постійному потенціалі -200 В, з додатковим високовольтним імпульсним потенціалом). Для вакуумно-дуговых покрытий на основе молибдена изучено влияние давления смешанной газовой атмосферы (80%C₂H₂+20%N₂) и высоковольтного отрицательного потенциала (подаваемого на подложку в импульсной форме) на элементный и фазовый состав, структуру и физико-механические характеристики формируемого материала. Показано, что в температурном интервале подложки при осаждении 400…550 °С в результате плазмохимических реакций максимальное содержание атомов азота в покрытии не превышает 1,5 ат.%. Выявлено, что при наибольшем давлении Р(C₂H₂+N₂)= 2.3∙10⁻¹ Па, когда формируется фаза γ-MoC, достигается сверхтвердое состояние 50,5 ГПа (при постоянном потенциале -200 В, без дополнительного высоковольтного импульсного потенциала) и 51,1 ГПа (при постоянном потенциале -200 В, с дополнительным высоковольтным импульсным потенциалом).